2014
DOI: 10.1007/s10943-014-9845-z
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level Interventions for Reconciling Conflicting Religious and Sexual Domains in Identity Incongruity

Abstract: Two of the most unstable domains involved in identity formation, the religious and sexual domains, come into conflict when vulnerable populations of the lesbian, gay, bisexual and transgender community experience oppression from the indoctrination of religious beliefs that persecute their sexual orientation. This conflict, aptly termed identity incongruity in this article's discourse, results in a schism that adversely affects these vulnerable populations. This paper investigates the roles of religion, spiritu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 36 publications
1
29
0
2
Order By: Relevance
“…Sin embargo, se postula que la modernización está gestando un proceso de liberalización social que incluye cambios de actitudes hacia la homosexualidad [39] . En este contexto, existen comunidades religiosas, iglesias y organizaciones que tienen una mayor apertura y un mensaje de bienvenida a la comunidad LGTB en distintas religiones [42] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Sin embargo, se postula que la modernización está gestando un proceso de liberalización social que incluye cambios de actitudes hacia la homosexualidad [39] . En este contexto, existen comunidades religiosas, iglesias y organizaciones que tienen una mayor apertura y un mensaje de bienvenida a la comunidad LGTB en distintas religiones [42] .…”
Section: Discussionunclassified
“…Ante este panorama se pueden plantear soluciones que involucren a líderes políticos, cívicos y religiosos que influyan en la opinión pública y el establecimiento de políticas sociales que eviten la persecución contra la comunidad LGTB [42] . Además, resulta importante generar un ambiente tolerante para las personas homosexuales en las iglesias con una postura de bienvenida, sobre todo para aquellas quienes viven un conflicto interno entre su religiosidad y su homosexualidad, lo cual permitiría una participación más activa en la iglesia y consolidaría su compromiso religioso y espiritualidad [49] .…”
Section: Discussionunclassified
“…Based on EST, our findings suggest strategies for intervention across the social ecology of bias-based bullying of SGMY (see Figure 1). Interventions that specifically address religious microsystems include the creation of safe, inviting, and inclusive spaces for ethnically diverse SGMY within religious institutions (Liboro, 2015; Ryan & Rees, 2012). Inclusive places of worship, such as the Metropolitan Community Church and el-Tawhid Unity Mosque in Toronto, synagogues such as Beit Simchat Torah in New York City and Beth Chayim Chadashim in Los Angeles, and organizations such as Soulforce, promote consistent messages supporting inclusion, social justice, and human rights.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusive places of worship, such as the Metropolitan Community Church and el-Tawhid Unity Mosque in Toronto, synagogues such as Beit Simchat Torah in New York City and Beth Chayim Chadashim in Los Angeles, and organizations such as Soulforce, promote consistent messages supporting inclusion, social justice, and human rights. Opportunities for positive engagement with religious institutions and spirituality—such as entreaties to SGMY to participate and serve in supportive faith-based programs (Ryan & Rees, 2012) and intergroup dialogue (Dessel, 2010)—may promote identity integration, with salutary implications for SGMY health (Dessel, Woodford, & Warren, 2011; Liboro, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many Catholic gay youth begin recognizing their sexual preference in high school and start experiencing an internal conflict between the religious and sexual domains of their forming identity. This internal conflict eventually leads to a dissonance between two of the most important domains of their forming identity, a distressing state that has been recognized as a form of identity incongruity (Liboro 2014). Studies have found that greater religiosity, particularly within the Catholic faith, has been linked to higher rates of internalized homophobia and homonegativity, delayed identity development and coming out, depression, and fragile psychological well-being (Kappler et al 2013;Wilkerson et al 2012).…”
Section: Homophobia Discrimination and The Catholic Churchmentioning
confidence: 99%